The influence of attitude: a sociological investigation of Reintegrative Shaming Theory - Miller, Jennifer (Kansas State University, 2010)
John Braithwaite developed the theory of reintegrative shaming in 1989. His hope was to develop a theory that better explained the complexities of crime such as the age curve, and high number of male offenders. Building from Braithwaite’s work, this thesis utilizes Reintegrative Shaming theory to explore how attitudes influence the reintegrative shaming process, and whether or not women, are more susceptible to shaming than men, as hypothesized by Braithwaite. It seeks to understand the role attitude plays in the reintegrative shaming process. This thesis hypothesizes that a reintegrative shaming punishment will positively impact an offender’s attitudes towards law, deterrence, law enforcement officials, and so on. Further, Braithwaite hypothesized that interdependent and communitarian individuals will be more susceptible to the impact of punishment (shaming); this relationship is also tested. Using data from the Reintegrative Shaming Experiments (RISE) in Australia, this thesis specifically studies the impact of sex and shaming punishment on attitudes towards the law and deterrence attitudes. In addition, information from RISE is used to test the relationships between interdependency and sex, and communitarianism and sex. The findings suggest mixed support for Reintegrative Shaming theory.
Keywords: Reintegrative Shaming Theory; Attitudes; Sociology, Criminology and Penology (0627)